Ecology and Bio-economics of Freshwater Apple Snail Pila globosa in Natore district of Bangladesh - Shathi, Umme Habiba; Rahman, Md. Redwanur (Journal of Sustainability and Environmental Management, 2022)
Pila globosa is an economically and commercially valued snail used as food in aquaculture, medicine, and food item in many regions of Bangladesh and other countries. The current study examines the ecology of Pila globosa and determines their current bio-economic situation. Pila globosa were collected from Singra, Lalpur and, Bagatipara upazila of Natore district. It was found 1.5-fold decline of the snail population in the study areas. Pila globosa is an ecological element that actively contributes to preserving a healthy aquatic habitat, which is necessary for biodiversity preservation. On the one hand, snail fauna scientific management is out of date. On the other hand, Pila globosa is still being exploited for fish culture, providing the underprivileged with a means of subsistence and the country with foreign income. By easing pressure on the natural population, the scenario justifies the development of supplemental Pila globosa culture techniques for commercial use.